Outcome Of Totally Extra-Peritoneal (TEP) Mesh Repair Among Patients With Unilateral Primary Inguinal Hernia: A Single Center Experience - Shah, Kunda Bikram; Basukala, Sunil; Yogi, Barurendra Raj; Malla, Srijan (Journal of Society of Surgeons of Nepal, 2023)
Introduction: Inguinal hernias were conventionally treated with open methods like hernioplasty and herniorrhaphy. However, with the development in minimal access surgery, the trends have changed and surgeons are also performing the TEP and TAPP laparoscopic hernia repair routinely. Hence, a retrospective study was performed to assess the safety, feasibility, and associated complications of the TEP laparoscopic hernia repair. Methods: A single institution, single unit retrospective study of all TEP hernia repair was performed at the department of surgery from May 2020 to April 2021. Data of all patients undergoing TEP were obtained from a proforma attached to the case file during patients’ admission and was analyzed. Results: A total number of 30 patients underwent the TEP laparoscopic hernia repair during the study period. Age group ranged from 25 years to 80 years and a male preponderance was noted with all patients being male. Per operative findings of indirect hernia was noted in 27, and direct hernia in 3 patients. The mean operating time was 76.23 ± 13.53 minutes. Complications encountered in the post-operative period were seroma in one patient, and wound erythema in two patients. The mean hospital stay was 1.6 ± 0.72 days. Conclusion: Totally Extra-peritoneal (TEP) laparoscopic repair can be performed and has all the established benefits of minimal access surgery among patients with primary unilateral inguinal hernia.